2019
DOI: 10.3390/en12112097
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Temperature Change and Crack Expansion of High Temperature Granite under Different Cooling Shock Treatments

Abstract: It is valuable to observe the influence of different cooling methods on the exploitation of geothermal energy and breaking hard rocks in deep geo-engineering. In this work, the effects of different cooling shock treatments on high temperature granite are discussed. First, perforated 100-mm-side cubic biotite adamellite samples were heated to four targeted temperatures (150 °C, 350 °C, 550 °C, and 750 °C). Then, anti-freeze solutions were compounded to produce the different cooling shock effects (20 °C, 0 °C, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…They found that cooling with water can reduce the mechanical properties of granite samples. Shen et al (2019) observed the influence of different cooling methods on granite after heat treatment. Their study showed that the effect of rapid cooling is much greater than the effect caused by slow cooling of heated granite.…”
Section: Previous Studiesmentioning
confidence: 99%
“…They found that cooling with water can reduce the mechanical properties of granite samples. Shen et al (2019) observed the influence of different cooling methods on granite after heat treatment. Their study showed that the effect of rapid cooling is much greater than the effect caused by slow cooling of heated granite.…”
Section: Previous Studiesmentioning
confidence: 99%
“…High values of α, together with high temperatures that reach the surface stones of the hamada and the cooling due to rain will produce a rapid surface contraction that causes the fragmentation of the Umm Bab Member. Texture, grain size and thermal dilatation of stones are the main factors that determine the rate of thermal decay due to, among other causes, physical-chemical processes that act to break bonds at cracks tips (Rong et al, 2018;Al-Omari et al, 2019;Jin et al, 2019;Peng et al, 2019;Shen et al, 2019). Cracking proceeds even when only extremely low stresses are applied to the stone (akin to very small pulling forces).…”
Section: Thermal and Hydric Dilatometrymentioning
confidence: 99%
“…Zhang et al (2019) mainly studied the influence of temperature and prefabricated cracks on the failure mode of granite, and explained the formation mechanism of different failure modes of granite under the combined action of temperature effect and cracks. Shen et al (2019) prepared antifreeze by adjusting the concentration of calcium chloride solution, and conducted cooling shock (20 °C, 0 °C and − 30 °C) on granite samples with target temperatures of 150, 350, 550 and 750 °C. The results showed that with the decrease of refrigerant temperature, the local distribution characteristics of granite macro cracking became more obvious.…”
Section: Introductionmentioning
confidence: 99%